2020
DOI: 10.1590/1806-9061-2019-1024
|View full text |Cite
|
Sign up to set email alerts
|

Supra-nutritional Levels of Selected B Vitamins in Animal or Vegetable Diets for Broiler Chicken

Abstract: The objective of this study was to evaluate the effects of supranutritional level of selected B vitamins in different types of diet on broiler performance. Two experiments were conducted using male and female one-day-old chicks (n=288 each; initial body weights in experiment I and II was, respectively, 47.57 ± 0.43, and 47.98 ± 0.31) reared in batteries up to 18 days. In experiment I, the chicks were fed a corn and soybean meal-based diet and, in experiment II, a diet containing oxidized animal by-product meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
1
4
0
2
Order By: Relevance
“…Furthermore, when compared to the control and other treated groups, the T5 group's total antioxidant capacity increased significantly. Muscle catalase activity, on the other hand, did not differ between experimental groups.This result is similar to other studies found that adding high concentration of riboflavin could increase antioxidant parameters like SOD, malondialdehyde and glutathione peroxidase [36].This finding is consistent with other studies that found that increasing antioxidant parameters such as SOD, malondialdehyde, and glutathione peroxidase by using a high concentration of riboflavin [37]. In addition, Gouda et al [38] discovered that feeding folic acid at a rate of 1.5 mg/kg for 35 days improved performance.And also, discovered that feeding 1.5 mg/kg folic acid for 35 days improved broiler antioxidant status by increasing heat shock protein 70 (HSP70), total antioxidant capacity (TAC), and superoxide dismutase enzyme (SOD) activity under heat stress.…”
Section: Antioxidant Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, when compared to the control and other treated groups, the T5 group's total antioxidant capacity increased significantly. Muscle catalase activity, on the other hand, did not differ between experimental groups.This result is similar to other studies found that adding high concentration of riboflavin could increase antioxidant parameters like SOD, malondialdehyde and glutathione peroxidase [36].This finding is consistent with other studies that found that increasing antioxidant parameters such as SOD, malondialdehyde, and glutathione peroxidase by using a high concentration of riboflavin [37]. In addition, Gouda et al [38] discovered that feeding folic acid at a rate of 1.5 mg/kg for 35 days improved performance.And also, discovered that feeding 1.5 mg/kg folic acid for 35 days improved broiler antioxidant status by increasing heat shock protein 70 (HSP70), total antioxidant capacity (TAC), and superoxide dismutase enzyme (SOD) activity under heat stress.…”
Section: Antioxidant Activitysupporting
confidence: 90%
“…[11]. Furthermore, supplementation of vitamins B2, B5, B3, B9, and B12 at supra-nutritional levels improved the productive performance of broiler chickens raised in batteries and fed a corn and soybean-based diet [12] . Because B complex vitamins play numerous roles, their deficiency has a significant impact on the host's metabolism.…”
Section: Introductionmentioning
confidence: 98%
“…The beneficial effects of volatile fatty acids on intestinal health, liver functions and tissue synthesis (Lee and Gemmell 1972;van der Wielen et al 2000) and possible functional properties of the micronutrients in blood and RD may be reasons for the pattern of growth performance observed in our study. Dietary vitamin B has been reported to improve the performance of poultry (Lindstrom et al 1949;Dryden and Hartman 1971;Patel and McGinnis 1977;Coelho and McNaughton 1995;Suckeveris et al 2020). The effect of B vitamins is mainly linked to their metabolic functions including cofactors of enzymatic reactions, metabolism of carbohydrates and amino acids, and synthesis of methyl groups and nucleic acids (Suckeveris et al 2020).…”
Section: Growth Performancementioning
confidence: 99%
“…Dietary vitamin B has been reported to improve the performance of poultry (Lindstrom et al 1949;Dryden and Hartman 1971;Patel and McGinnis 1977;Coelho and McNaughton 1995;Suckeveris et al 2020). The effect of B vitamins is mainly linked to their metabolic functions including cofactors of enzymatic reactions, metabolism of carbohydrates and amino acids, and synthesis of methyl groups and nucleic acids (Suckeveris et al 2020).…”
Section: Growth Performancementioning
confidence: 99%
“…It is required to supplement B vitamins in chickens' meal to ensure maximum production potential. Different forms of vitamin B such as riboflavin, pantothenic acid, folate, B12 and niacin improved production performance of chickens fed with low density diet (Suckeveris et al, 2020). Vitamin B1 (thiamine) can be classified as part of the anti-stress vitamins due to its strong antioxidant ability (Lukienko et al, 2000).…”
Section: Vitamin Bmentioning
confidence: 99%